Overwintering Physiology and Cold Tolerance of the Sunn Pest, Eurygaster integriceps, an Emphasis on the Role of Cryoprotectants - Hasanvand, Hamzeh; Izadi, Hamzeh; Mohammadzadeh, Mozhgan (Frontiers in Physiology, 2020)
As a serious pest of wheat, the Sunn pest, Eurygaster integriceps Puton (Hem.: Scutelleridae), is prevalent in Iran. This pest belongs to univoltine species and tends to aestivate and overwinter in high altitudes of nearby mountains as diapausing adults. The economic importance of the crop attacked by this pest, i.e. wheat led the authors to study the physiological adaptations of these diapausing adults, that is, changes in the supercooling point (SCP), in the accumulation of cryoprotectants, and in the activities of the related enzymes in relation to diapause development. The mean SCP of the diapausing adults was found to be -8 ºC. The lowest SCP, i.e. approximately -11 ºC, was observed in the middle of diapause, October, when the highest cold hardiness was also interestingly recorded. This finding proposed that SCP depression could be a feasible cold-tolerance strategy for diapausing adults. The sugar content was high in the initiation and at the termination of diapause and was low during diapause maintenance. These sugar reserves were most likely utilized to be converted to glycogen and lipid during diapause maintenance as a survival strategy. The changes in the glycogen and lipid contents were inversely proportional to the changes in the total sugar content. The authors also found that the changes in the glycogen content were directly proportional to those in the low-molecular-weight carbohydrates (e.g. glycerol and trehalose) and in the diapause development. This finding underlined the role of the low-molecular-weight carbohydrates, such as the cryoprotectants, in enhancing the cold tolerance of the given insect. In this study, the diapause-associated changes in the activities of α-amylases and proteases were also investigated. The results showed that the enzyme activities were related to diapause development and cold-tolerance enhancement. The highest enzyme activity was observed in September. Since the overwintering adults of the Sunn pest could not tolerate temperatures below their SCPs, they were grouped in the freeze-intolerant species.